Investigating the Allelopathic and Bioherbicidal Potential of Solidago altissima with a Focus on Chemical Signaling in Trifolium repens - Ho-Jun Gam; Arjun Adhikari; Yosep Kang; Md. Injamum-Ul-Hoque; Shifa Shaffique; Ji-In Woo; Jin Ryeol Jeon; Byeong-Kwan An; Min Young Back; Ki-Yong Kim; Sang-Mo Kang; In-Jung Lee (Plants)
Invasive weed species exhibit both advantages, such as the potential for allelochemicals in bioherbicide development, and risks, including their threat to crop production. Therefore, this study aims to identify an allelochemical from Solidago altissima, an invasive weed species. The dose-dependent effects of S. altissima shoot and root extracts (SSE, SRE) on the signaling in the forage crop Trifolium repens and germination in various weed species (Echinochloa oryzicola, Cyperus microiria, Alopecurus aequalis, Portulaca oleracea, and Amaranthus retroflexus) were evaluated. The results showed that the T. repens seedlings treated with root extracts exhibited a significant decrease in plant height, dry weight, and chlorophyll content, along with an increase in H2O2 levels. Additionally, antioxidant activities, such as superoxide dismutase, catalase, and peroxidase enzyme activities, were significantly elevated in T. repens treated with SRE. Moreover, SRE treatment significantly inhibited the seed germination of all tested weed species in a concentration-dependent manner. Gas chromatography-mass spectrometry analysis of S. altissima root extract identified a high concentration of methyl kolavenate, a clerodane diterpene predicted to act as a phytotoxic agent. These findings highlight the potential of S. altissima for the development of crop-protective agents while emphasizing its potential risks in agriculture.